A covalent heterostructure of monodisperse Ni2P immobilized on N, P-co-doped carbon nanosheets for high performance sodium/lithium storage. (June 2018) - Shi, Shanshan; Li, Zhiping; Sun, Yong; Wang, Bo; Liu, Qiunan; Hou, Yanglong; Huang, Shifei; Huang, Jianyu; Zhao, Yufeng
Abstract: The high volume expansion and serious agglomeration during sodiation/lithiation of transition metal phosphides (TMPs) raise up challenging kinetic issues and rapid capacity fading upon cycling. The good dispersion and confined movement of individual TMP particles are critical in mitigating the agglomeration, which however have been rarely concerned. In this work, we report a novel covalent heterostructure with monodisperse Ni2 P immobilized on N, P-co-doped carbon nanosheets (Ni2 P@NPC), which exhibits a remarkable reversible discharge capacity and outstanding long-term durability for both sodium storage (361 mA h g -1 @100 mA g -1 after 300 cycles, and 181 mA h g −1 @500 mA g -1 after 1200 cycles) and lithium storage (1555 mA h g -1 @100 mA g -1 after 130 cycles, and 603 mA h g -1 @1000 mA g -1 after 800 cycles). Most importantly, using the in-situ TEM visualized technique, we demonstrate that the immobility and monodisperse nature of Ni2 P are responsible for the agglomeration-free charge storage process upon cycling. The density functional theory (DFT) calculations reveal the strong covalent coupling between Ni2 P and NPC, which realizes the electronic structure engineering of both TMP and carbon buffer, and uncovers the origin of long-term stability and outstanding capacity. Graphical abstract: A smart design of monodisperse Ni2 P nanocrystals covalently immobilized on N, P-codoped carbon nanosheet (Ni2 P@NPC) has the potential for high performance energy storage. The good dispersion and confined movement of individual TMP particles enable the Ni2 P@NPC with an agglomeration free charge storage process upon cycling, which performs outstanding specific capacities and long-term durability for both sodium and lithium storage. fx1 Highlights: Ni2 P nanocrystals are covalently immobilized on N, P-codoped carbon nanosheets. The as prepared material demonstrates high sodium/lithium storage performance. In-situ TEM study visualized the agglomeration-free charge storage process. The DFT calculations uncovered the origin of outstanding stability and capacity.